The Element of Politeness in Novel The Perks of Being a Wallflower - Andi Tenriuji; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2021)
The objective of this study were to analyze the type of politeness principle used and how the politeness principle use in the novel written by Stephen Chbosky. The data source used in this research is The Perks of Being a wallflower novel. In analyzing the data, the writer used a qualitative descriptive research method through a sociopragmatic approach. The data were obtained by using reading, collecting, and analyzing techniques and to classify the politeness principle in the novel by Geoffrey Leech theory. The result of this research were 28 utterance that contain maxim of politeness principle where 6 utterance of tact maxim, 2 utterance of generosity maxim, 5 utterances of approbation maxim, 5 utterances of modesty maxim, 6 utterance of agreement maxim and 4 utterance of sympathy maxim. Furthermore, the characters use the politeness by follow measurement of the pragmatic scale to express their politeness. Those pragmatic scale are the cost benefit scale, the optionally scale, indirectness scale and social distance scale.